Variability in surface electromyography of right arm biceps brachii muscles between male adolescent, vicenarian and tricenarian with distinct electrode placement - Nizam Uddin, Ahamed (IEEE Conference Publications, 2014)
Link to publisher's homepage at http://ieeexplore.ieee.org/